High potential of stable carbon sequestration in phytoliths of China's grasslands. (31st January 2022) - Song, Zhaoliang; Wu, Yuntao; Yang, Yuanhe; Zhang, Xiaodong; Van Zwieten, Lukas; Bolan, Nanthi; Li, Zimin; Liu, Hongyan; Hao, Qian; Yu, Changxun; Sun, Xiaole; Song, Alin; et al.
Abstract: Phytolith carbon (C) sequestration plays a key role in mitigating global climate change at a centennial to millennial time scale. However, previous estimates of phytolith‐occluded carbon (PhytOC) storage and potential in China's grasslands have large uncertainties mainly due to multiple data sources. This contributes to the uncertainty in predicting long‐term C sequestration in terrestrial ecosystems using Earth System Models. In this study, we carried out an intensive field investigation (79 sites, 237 soil profiles [0–100 cm], and 61 vegetation assessments) to quantify PhytOC storage in China's grasslands and to better explore the biogeographical patterns and influencing factors. Generally, PhytOC production flux and soil PhytOC density in both the Tibetan Plateau and the Inner Mongolian Plateau had a decreasing trend from the Northeast to the Southwest. The aboveground PhytOC production rate in China's grassland was 0.48 × 10 6 t CO2 a –1, and the soil PhytOC storage was 383 × 10 6 t CO2 . About 45% of soil PhytOC was stored in the deep soil layers (50–100 cm), highlighting the importance of deep soil layers for C stock assessments. Importantly, the Tibetan Plateau had the greatest contribution (more than 70%) to the PhytOC storage in China's grasslands. The results of multiple regression analysis indicated that altitude and soil texture significantly influenced the spatial distribution of soil PhytOC, explaining 78.1% of the total variation. Soil phytolith turnover time in China's grasslands was mainly controlled by climatic conditions, with the turnover time on the Tibetan Plateau being significantly longer than that on the Inner Mongolian Plateau. Our results offer more accurate estimates of the potential for phytolith C sequestration from ecological restoration projects in degraded grassland ecosystems. These estimates are essential to parameterizing and validating global C models. Abstract : Phytolith‐occluded carbon (PhytOC) plays an important role in long‐term terrestrial carbon sequestration. The Tibetan Plateau accounts for more than 70% of the total PhytOC across China's grasslands. Ecological restoration projects across China's grasslands have significant sequestration potential by PhytOC.